On the Voluntary and Involuntary Provision of Public Goods - Bernheim, B. Douglas (American Economic Review, 1986)
This paper extends preexisting results concerning voluntary private funding of public goods. The assumption that individuals care about the magnitude of their own contributions only insofar as these contributions affect the aggregate level of expenditures is shown to have untenable implications. The analysis suggests that a reexamination of the factors that motivate individuals to make contributions is in order.